The Impact of Regional Structure and Topography on the Effectiveness of Public Transportation Services - Ilham, Ilham (West Science Social and Humanities Studies, 2024)
This study investigates the impact of urban structure and topography on public transportation effectiveness in developing countries. Using structural equation modeling analysis of survey data from 500 public transit users across five diverse cities, we examine how these geographical factors influence accessibility, reliability, comfort, and user satisfaction. Results indicate that both urban structure and topography significantly affect transportation effectiveness, with urban structure having a slightly stronger influence. Polycentric urban designs and moderate topography were associated with higher public transit effectiveness. User perceptions highlighted the importance of integrated planning approaches. The findings suggest policymakers should consider geographical contexts when designing public transportation systems, potentially through adaptive infrastructure and context-specific service models. This research contributes to a more nuanced understanding of public transit planning in varied urban environments of developing nations.